Analysis of Numeracy Literacy in Developing Students Mathematical Creativity in Elementary School - Anwar Saifullah; Meggy Novitasari (Lembaran Ilmu Kependidikan, 2025)
Numeracy literacy plays a crucial role in developing students’ mathematical creativity in elementary school. However, students’ numeracy skills remain relatively low and require focused attention in the learning process. This study aims to analyze the role of numeracy literacy in enhancing the mathematical creativity of elementary school students. A descriptive qualitative approach was employed, involving upper-grade elementary school students and teachers as research subjects. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The results show that numeracy literacy—which includes the ability to understand, interpret, and apply mathematics in real-life contexts—significantly contributes to fostering students' creative mathematical thinking. Students’ mathematical creativity is reflected in their ability to generate alternative solutions, develop problem-solving strategies, and express ideas logically. The study concludes that numeracy literacy not only strengthens conceptual understanding of mathematics but also serves as a medium to cultivate students’ creative thinking. The novelty of this research lies in its focused analysis of the relationship between numeracy literacy and mathematical creativity in the context of elementary education, an area that has been relatively underexplored in previous studies.